In situ phase interface engineering of MoLa alloys for enhanced strength. (January 2023) - Li, Kai; He, Dongyang; Liu, Hailang; Wu, Zhuangzhi; Wang, Dezhi
Abstract: Incoherent interphases and oxygen segregation at the grain boundaries (GBs) significantly deteriorate the strength of Mo-based alloys. In this study, a new additive, LaB6, was proposed to enhance the mechanical properties. It was found that LaB6 reacted with the matrix to generate coherent La2 O3, volatile B2 O3 and tiny MoB in situ during sintering. The addition of LaB6 does not increase strength by itself, but can limit grain growth and construct a coherent interface between the as-obtained La2 O3 and Mo matrix. More importantly, the oxygen impurity is removed by B in the form of B2 O3, which purifies the GBs. As a result, the as-sintered Mo-La-B billets present an extremely high ultimate tensile strength of 965 MPa, which is among the best recorded values for all sintered Mo-based alloys. The enhanced strength can be attributed to the refined grain size, coherent phase interface, and purified GBs. Highlights: LaB6 reacts with matrix to produce coherent La2 O3, volatile B2 O3, and tiny MoB in situ . The strength is enhanced by the formation of La2 O3 but not the additive LaB6 itself. The additive LaB6 leads to coherent interface between as-gained La2 O3 and Mo matrix. The optimized Mo-La-B billets present an ultimate tensile strength of 965 MPa.